(untitled) (Faridpur Medical College Journal, 2014)
Anorectal malignancies that require abdominoperineal resection (APR) is very common. Laparoscopic APR can be a better option. Laparoscopic APR has been seldom studied. This study aims to evaluate perioperative and early postoperative outcomes of laparoscopic APRs performed for the treatment of ano-rectal carcinomas. Patients operated for ano-rectal carcinoma between June 2011 to June 2013 in Bangabandhu Sheikh Mujib Medical University (BSMMU) were observed. Demographics, tumor and procedure-related parameters, perioperative results, early postoperative outcomes and survival were observed. Total 22 patients were under went laparoscopic APR. Male: Female ratio was 15:7 (68.18%: 31.82%). Age range was from 30-65 years with a mean age of 36.55 years. Mean operation time was 165 minutes and mean post-operative hospital stay was 6.8 days. Overall complication rate was 45.45%. Laparoscopic APR is a safe, effective and technically feasible procedure. It can be a better operative procedure than open APR. DOI: http://dx.doi.org/10.3329/fmcj.v8i2.20281 Faridpur Med. Coll. J. 2013;8(2): 53-55